An Interactive Digital Storytelling approach to explore books in Virtual Environments (Informatica, 2016)
This paper presents the design and the architecture of an educational 3D application enabling reading books in Virtual Environments exploiting an Interactive Digital Storytelling paradigm, in order to disseminate culture using an entertaining approach particularly suitable for young people. We also present two case studies using this approach: the first one is related to the Lonicer’s Kreuterbuch, a XVI century medicine manuscript; the second one is a book composed by three fables written by Lev Tolstoy. The paper presents also a preliminary usability test in order to evaluate the suitability of such an approach in terms of engagement and comprehension.